Sistem Pakar Identifikasi Gangguan Pencernaan Anjing Dengan Metode Forward Chaining Berbasis Android - Nabiladika Naufal Rafif; Laila Isyriyah; Febry Eka Purwiantono (J-INTECH ( Journal of Information and Technology), 2020)
Dog is a not popular animal pet in Indonesia, there are many neglected dog that need help in Indonesia. There are many dog owner that lack information about dog diseases, even though there are many disease that can give the dog a complication or even worst dead when not treated quickly. The lack of accurate information about dog diseases made many people joint a dog owners community, naturally there are some misinformation and inaccurate information there. Based on foreign and domestic study, type of dog diseases that come to animal hospital is digestive system diseases. Around 35% of the data from dog that treated in animal hospital suffer from digestive system diseases. This study aims are people who looking for information about dog can be helped and dog that suffer from disease can be quickly treated.